2019
DOI: 10.1136/bmjopen-2019-034344
|View full text |Cite
|
Sign up to set email alerts
|

How representative are colorectal, lung, breast and prostate cancer patients responding to the National Cancer Patient Experience Survey (CPES) of the cancer registry population in England? A population-based case control study

Abstract: ObjectiveTo assess the representativeness of National Cancer Patient Experience Survey (CPES) responders compared with the English cancer registry population in term of age, sex, socioeconomic deprivation, ethnicity, disease stage and median survival.DesignPopulation-based case-control study.SettingEngland.PopulationWe identified 103 186 colorectal, lung, breast and prostate cancer patients responding to at least one survey during 2010–2014 and randomly selected one non-responder from the cancer registry match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 18 publications
3
21
0
Order By: Relevance
“… 47 These findings about the limitations of CPES representativeness were also confirmed by two other studies that compared the survey responders to the general cancer population of the same cancer in England. 48 , 49 These studies found patients who are included in CPES tend to be less deprived, more likely to be from a white background, and to have better prognoses. 48 , 49 Survey methodology and the timing of response were also shown to influence patients’ reported experiences.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 47 These findings about the limitations of CPES representativeness were also confirmed by two other studies that compared the survey responders to the general cancer population of the same cancer in England. 48 , 49 These studies found patients who are included in CPES tend to be less deprived, more likely to be from a white background, and to have better prognoses. 48 , 49 Survey methodology and the timing of response were also shown to influence patients’ reported experiences.…”
Section: Resultsmentioning
confidence: 99%
“… 48 , 49 These studies found patients who are included in CPES tend to be less deprived, more likely to be from a white background, and to have better prognoses. 48 , 49 Survey methodology and the timing of response were also shown to influence patients’ reported experiences. Patients who responded online reported better overall experience of care than those who responded through mail.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations